A Study on the Problems Faced by Coffee Planters in Chikmagalur District - H N, Reena Patel; H N, Reena Patel; S, Sri Ranjini (International Journal of Psychosocial Rehabilitation, 2020)
It is of common knowledge that coffee is grown in several parts of the State of Karnataka in India against various geological and climatic conditions. Chikmagalur, a district in Karnataka state, India is the birth place of coffee in the country. It is where the coffee is grown in shade, by preserving native vegetations. Chikmagalur is situated in the western region of Karnataka state. This district attracts many tourists due to scenic locations and nearby hill stations such as Baba Buda Giri, Kudremukha, Mullayangiri and many places.In the recent years, extremely unpredictable and adverse climatic changes happening in the country have contributed to frequent flare up of diseases, labour and other problems in Chikmagalur district.A deep understanding of plant ecology, physiology and pathology among the coffee growers was never as indispensable as it is today. The cultural operations which hitherto have been linked to months and weeks during a year are increasingly getting linked to the prevalence to the specific climatic conditions and various aspects of coffee plants.This study makes an attempt to analyse the problems of coffee planters in Chikmagalur district due to lack of labour, finance, natural calamities and the effects of government policies in coffee production.